Improving Digital Safety and Ethical Awareness through Community Service Initiatives in Educational Environments - Rozy, Nurul Faizah; Bakti, Andi Faisal; Azhari, Muhammad; Khairani, Dewi; Sulistiya, Noeni Indah; Zulhazmi, Abraham Zakky (Mimbar Agama Budaya, 2025)
This study presents the outcomes of a community service initiative conducted by Informatics Engineering students of UIN Jakarta, focusing on the enhancement of digital literacy—particularly digital safety and digital ethics—within the cultural context of Indonesian educational institutions. The program engaged nine schools across Jakarta, Tangerang City, South Tangerang, and Bogor, regions characterized by diverse educational and socio-cultural backgrounds. Emphasizing culturally sensitive approaches to digital interaction, the program provided participants with knowledge and ethical frameworks aligned with local values and community norms. Post-program evaluations revealed a marked increase in digital literacy, with an average score of 4.28 on a 5-point scale. Furthermore, 47.1% of participants rated the module on data security at the highest level. However, cultural barriers were also identified, including hesitancy from some institutions to adopt formal digital supervision structures, often due to traditional perceptions of trust and authority. Despite these challenges, the initiative proved effective in cultivating culturally-aware digital behavior, preparing participants to navigate the digital era while remaining rooted in local ethical standards.